Toyotism and Brahminism: Employee relations difficulties in establishing lean manufacturing in India - Kunju Kunju Mathew, Sagi; Jones, Robert (Emerald, 2012)
Purpose – The purpose of this paper is to analyse the cross-cultural reasons underlying the extreme industrial unrest experienced during the first seven years of Toyota’s operations in India. Design/methodology/approach – The paper employs a case study approach using data obtained from 30 personal interviews, field notes, observations, and internet media sources. Findings – The paper reports how Toyotism shares three common features with Brahminism – renunciation, performance, and perfection – and how antipathy towards the manner in which these features were implemented in India caused significant resistance amongst the production workforce. Research limitations/implications – The paper has implications for academics and practitioners in helping to understand how employee relations, unrest and antagonism towards lean manufacturing practices are closely related to cross-cultural issues prevalent in host countries. Originality/value – The concept of Brahmanism in Indian employee relations is under-researched in comparison with other aspects of Indian culture and antipathy towards the concept as a source of resistance to the implementation of lean systems needs to be better understood.